Unbalanced Arginine pathway and altered maturation of pleural macrophages in Th2-deficient mice during Litomosoides sigmodontis filarial infection - Remion, Estelle; Gal, Joséphine; Chaouch, Soraya; Rodrigues, Jules; Lhermitte-Vallarino, Nathaly; Alonso, Joy; Kohl, Linda; Hübner, Marc P.; Fercoq, Frédéric; Martin, Coralie (Frontiers in Immunology, 2022)
Filarial parasites are tissue dwelling worms transmitted by hematophagous vectors. Understanding the mechanisms regulating microfilariae (the parasite offspring) development is a prerequisite for controlling transmission in filarial infections. Th2 immune responses are key for building efficient anti-parasite responses but have been shown to also lead to detrimental tissue damage in the presence of microfilariae. Litomosoides sigmodontis, a rodent filaria residing in the pleural cavity was therefore used to characterize pleuropulmonary pathology and associated immune responses in wild-type and Th2 deficient mice. Wild-type and Th2-deficient mice (Il-4rα-/-/Il-5-/-) were infected with L. sigmodontis and parasite outcome was analyzed during the patent phase (when microfilariae are in the general circulation). Pleuropulmonary manifestations were investigated and pleural and bronchoalveolar cells were characterized by RNA analysis, imaging and/or flow cytometry focusing on macrophages. Il-4rα-/-/Il-5-/- mice were hypermicrofilaremic and showed an enhanced filarial survival but also displayed a drastic reduction of microfilaria-driven pleural cavity pathologies. In parallel, pleural macrophages from Il-4rα-/-/Il-5-/- mice lacked expression of prototypical alternative activation markers RELMα and Chil3 and showed an altered balance of some markers of the arginine metabolic pathway. In addition, monocytes-derived F4/80intermediate macrophages from infected Il-4rα-/-/Il-5-/- mice failed to mature into resident F4/80high large macrophages. Altogether these data emphasize that the presence of both microfilariae and IL-4R/IL-5 signaling are critical in the development of the pathology and in the phenotype of macrophages. In Il-4rα-/-/Il-5-/- mice, the balance is in favor of parasite development while limiting the pathology associated with the host immune response.